The judicial peace settlement under the United Nations convention on the law of the sea (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Historically, maritime disputes have revolve around the use of the seas and the affirmation of the idea of freedom of navigation and control over larg parts of the seas, this led to the need to develop a legal regime for the settlement of international disputes to establish specific rights and obligations of states in their use of various maritime spaces for peaceful purposes, leading to the adoption of an integrated system of judicial settlement of  disputes embobied in the United Nations convention on the law of the sea 1982, which tried to establish a balance and to oblige states to settle peacefully by giving them the freedom to choose between multiple means, that its main feature is the creation of new judicial means, such as specialized  international tribunals for the settlement of disputes relating to the interpretation and application of the convention, as well as basic judicial means.